More efficient way of clean hydrogen production: The synergetic roles of magnetic effects and effective catalysts - Temiz, Mert; Kara, Aysegul Yagmur Goren; Erdemir, Dogan; Dincer, Ibrahim (ELSEVIER SCI LTD, 2024)
Clean energy sources are not the silver bullet; however, hydrogen has the potential to complete the equation with clean energy sources to achieve sustainability as an ultimate goal. Increasing efforts are made to achieve clean hydrogen production through water electrolysis in a feasible and sustainable manner. Water electrolysis appears to be a potential solution, which needs to be improved in order to achieve the performance targets. The current study uses data from experimental studies in the openly available literature to comparatively assess the catalysts along with the magnetic field effect to show how these additions can mitigate the inefficiencies of the water electrolysis process. The magnetic field effect is a recent topic that is discussed to improve the water electrolysis process, especially on the anode side, mainly due to the paramagnetic behavior of oxygen. This study investigates the magnetic field effects and compares them with the other effects of catalysts in order to present their impact on the overall water electrolysis process efficiency. Catalysts are then categorized and comparatively assessed in a case study with normalized parameters, both in their category and overall. Due to the behavior of different electrodes, different catalysts are considered on different sides. For the anode side, especially the catalysts with ferromagnetic elements performed better in a case study, where NiZnFe4Oxbrings a 6.54% energy efficiency improvement. The PtNi(N) nanowires, with a 4.79% energy efficiency improvement, can be highlighted among the cathode side catalysts. For the catalyst couples, there is a potential of more than 10% of energy efficiency improvement compared to the base case scenario.
Keywords: Hydrogen; Catalysts; Magnetic field; Energy; Environment; Sustainability; Efficiency; aq aqueous; MOS2 ULTRATHIN NANOSHEETS; EVOLUTION REACTION; OXYGEN; NI; ELECTROCATALYST; NICKEL; ALLOYS; IRON; Energy & Fuels; Engineering